2014
DOI: 10.1007/s12011-014-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Proteolytic Enzymes in Embryonic Axes of Germinating Bean Seeds under Copper Stress

Abstract: The changes in protease activities in embryonic axes during the first days of bean (Phaseolus vulgaris L.) seed germination were investigated in response to copper stress. Synthetic substrates and specific protease inhibitors have been used to define qualitatively and quantitatively different catalytic classes, particularly endoproteases (EP), carboxypeptidases (CP) and aminopeptidases (AP), then identify which ones were affected in the presence of copper. In fact, a failure in storage proteins mobilization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…For example, an excess of Cu, according to many researchers, leads to a reduction in seed germination [ 57 , 58 , 59 , 60 ]. In germinating seeds, Cu interferes with the release of nitrogen from the storage tissue, affecting not only the development of the seed embryo, but also the overall activity of proteases [ 61 ]. It induces the mobilization of biomass by the release of glucose and fructose, thus inhibiting the breakdown of starch and sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an excess of Cu, according to many researchers, leads to a reduction in seed germination [ 57 , 58 , 59 , 60 ]. In germinating seeds, Cu interferes with the release of nitrogen from the storage tissue, affecting not only the development of the seed embryo, but also the overall activity of proteases [ 61 ]. It induces the mobilization of biomass by the release of glucose and fructose, thus inhibiting the breakdown of starch and sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…It was also suggested that Cu ions inhibited the pathway related to the aminopeptidases activitiesnamely, the ubiquitin-proteasome pathway. 4,20 Cd is one of the toxic metals, contaminating ecosystem and causing chronic effects in plants, animals, and humans. In plants, it inhibits several physiological processes (e.g.…”
Section: Profiles Of Aminopeptidases Activity During Oilseed Rape Germination Under Standard Conditionsmentioning
confidence: 99%
“…The mobilization of seeds' reserves, to provide a sufficient level of nutrients, allocation of nitrogen sources to seedlings, and as a defensive process against environmental stresses, is an extremely important activity in the germinating plants. [3][4][5] It has been proven that aminopeptidases are crucial in the processes of germination, meiosis, flowering, aging, stress response and defense in different species. [6][7][8][9][10] Some of the enzymes, crucial for germination process, are synthesized either during embryogenesis (and further activated during imbibition) or just during imbibition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation